PENGUKURAN INDEKS KEPUASAN PENGGUNA DATA TERHADAP PELAYANAN PADA BADAN PUSAT STATISTIK KOTA SURAKARTA - Nugroho, Sidiq Permono; Syamsudin, Syamsudin (Universitas Muhammadiyah Surakarta, 2016)
This research aims was to figure out userâs satisfaction index towards this public service toward Central Bureau of Statistics (BPS). BPS is a non-ministry government institution implements the bureaucracy reform, and provides comprehensive, accurate, and sophisticated statistics in order to create a System of National Statistics. The data analysis technique for this research is Users (people who once used The Central Bureau of Statistic Service) Satisfaction Index, counted through weighted average values of some service elements based on Number 63/KEP/M.PAN/7/2003. Among the 120 users of The Central Bureau of Statistics, this research shows that The Satisfaction Index reaches 75.31 (good), but it still need to be improved remember there are some indicators showing a not quite good Performance Index. Totally 20 out of 24 indicators are categorized into âgood serviceâ, while the other fours indicator need to be enhanced and improved.